Penerapan Isometrik Handgrib Exercise Untuk Penurunan Tekanan Darah Pada Klien Dengan Hipertensi Di Puskesmas Kopeta - Holydiaz Tapun, Anastasia; Vianitati, Pasionista (Jurnal Keperawatan Duta Medika, 2025)
Introduction: Hypertension or high blood pressure is a non-communicable disease (NCD) that is a global health issue. A person is considered hypertensive when their blood pressure is >140/90 mmHg. One of the non-pharmacological therapies for lowering blood pressure is Isometric Exercise. Administering this nursing intervention can lower blood pressure in hypertensive patients. Objective: To implement family nursing care with Isotonic Handgrip Exercise to lower blood pressure in clients with hypertension at Puskesmas Kopeta. Method: The research used is descriptive with a case study approach. Data collection techniques included interviews, observations, physical examinations, and document studies. Results: Research from two hypertensive clients before the intervention showed results: Client I had a blood pressure of 150/95 mmHg, and Client II had 157/98 mmHg. After the intervention, the results were: Respondent I had 140/83 mmHg, and Respondent II had 145/94 mmHg. Conclusion: Isometric handgrip exercise has an effect on lowering blood pressure.